MECHANOCHEMICAL SYNTHESIS OF CEO2 NANOPOWDER USING PLANETARY BALL MILLING - Rahmahwati, Cut (Jurnal Sains dan Teknologi Reaksi, 2007)
Nanocrystalline cerium dioxide (CeO2) had been successfully synthesized by mechanochemical technique at  12, 24, 36, 48 and 60 hours milling times. The starting materials, hydrated cerium carbonate and sodium hydroxide, were mixed in weight ratio of 4:1 and were milled in a planetary ball mill with ball to powder ratio of 10:1. The high energy impact forces provided by the milling media caused collision of starting materials and allowed the chemical reaction to occur thus produced nanocrystalline cerium dioxide. The products were characterized using a battery of characterization method, including thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), X-ray diffraction (XRD), and gas adsorption-desorption measurement. The nanocrystalline CeO2 with 6.7 nmof crystallite size and specific surface area of 66.66 m2/g was obtained when the sample was milled for60 hrs and annealed in air at 350oC. The result showed that the crystallinity of nanocrystalline CeO2decreased with increasing the milling time.Keywords: Mechanochemical, planetary ball mill, milling time, nanocrystalline cerium dioxide.